Differences in Trauma in Boys and Girls 12-13 Years of Age - Mega Lestari; Nunung Siti Sukaesih; Sri Wulan Lindasari (Fakultas Keperawatan Universitas Andalas, 2025)
Elementary school-aged children are very vulnerable to experiencing unpleasant events and are often victims of violence. In Indonesia, West Java Province is ranked first in cases of violence against children, with a total of 1,695 victims. In Sumedang Regency, especially North Sumedang District, there is a high number of cases of violence against children. Children aged 12-13 are in the transition phase from children to adolescents. This study aims to analyze the differences in trauma in boys and girls aged 12-13 years. The method used in this study is a comparative quantitative method with a cross-sectional approach. The sampling technique in this study used Simple Random Sampling with a sample size using the calculation of the Krecji table with a significance level of 5%, namely 276 grade 6 elementary school children consisting of 133 boys and 143 girls. The instrument used in this study is the Childhood Trauma Questionnaire Short Form (CTQ-SF) questionnaire, which measures five dimensions of trauma, namely emotional abuse, physical abuse, sexual abuse, physical neglect, and emotional neglect. Data collected through questionnaires were analyzed using the Mann-Whitney U Test. The results of this study showed that there were significant differences in trauma between boys and girls aged 12-13 years in the dimensions of Emotional Abuse (p = 0.029), Physical Abuse (p < 0.001), and Physical Neglect (p < 0.001). There are differences in trauma in boys and girls. Boys are more vulnerable to physical trauma, and girls are more vulnerable to emotional or psychological trauma.